Investment Strategy In Capital Market (2024) - Tamara, Agina (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
The aim of this research is to find out the benefits of people's decisions in choosing the right investment in the capital market. Investor uses strategy and a certain technique to analyze different situation and condition happened between one and other exchange companies. The strategy is developed based on experiences, research result, analysis, and market surveys in a certain period. Articel is the first part of three series which presents, evaluate, examine of the strategy, and consider tactics in sharing share on the market. It is concluded that the investor should use money as loan that should be payed as soon as possible for the sake of its interests. This research is quantitative research. The main data source for this research comes from research questionnaires that have been filled out by respondents. Apart from that, data was also obtained from literature studies and documentation related to this research. By knowing investment strategies in the capital market, the results can determine what strategies are good and appropriate for investing in the capital market.